1982
DOI: 10.1302/0301-620x.64b4.7096429
|View full text |Cite
|
Sign up to set email alerts
|

Observations upon the interface between bone and polymethylmethacrylate cement

Abstract: The occurrence of a radiolucent line One of the knees was studied histologically. In the light of the universal observation of macrophages at bone-cement interfaces and the recent finding that osteoclasts are derived from macrophages, these observations are significant in relation to the aetiology of bone-cement lucencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
125
2
3

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(133 citation statements)
references
References 18 publications
3
125
2
3
Order By: Relevance
“…We have demonstrated, however, that large numbers of macrophages may be seen immediately next to the main cement mass in the absence of giant cells. These findings confirm our earlier observation (Freeman et al 1982) and those of Linder & Hansson (1983) that the presence of nonparticulate PMMA cement at a surgically immobile bone-cement interface may induce a macrophage response. The presence of these macrophages, though visible by hematoxylin-eosin staining, is made much more obvious when acid phosphatase staining of frozen sections is used.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have demonstrated, however, that large numbers of macrophages may be seen immediately next to the main cement mass in the absence of giant cells. These findings confirm our earlier observation (Freeman et al 1982) and those of Linder & Hansson (1983) that the presence of nonparticulate PMMA cement at a surgically immobile bone-cement interface may induce a macrophage response. The presence of these macrophages, though visible by hematoxylin-eosin staining, is made much more obvious when acid phosphatase staining of frozen sections is used.…”
Section: Discussionsupporting
confidence: 93%
“…Macrophages are known to accumulate at the bone-PMMA interface in response to polyethylene-wear debris and particulate cement (Revell 1982, Vernon-Roberts & Freeman 1976, Willert 1973, Willert et al 1974. We (Freeman et al 1982) and others (Linder & Hansson 1985) have recently observed the presence of macrophages at clinically well-fixed cemented components. These observations stimulated us to review the histologic appearance at a series of clinically stable well-fixed components that came to revision in an attempt to define the significance of the presence of macrophages at the clinically stable interface.…”
Section: Introductionsupporting
confidence: 54%
“…Unfortunately, although PMMA cement is strong in compression, its long-term strength may be limited under shear force vectors, 9 because there is histologic evidence that PMMA does adhere to bone. 22 At present, there are no current reports of failed sacroplasty for the treatment of SIFs, and sacroplasty has been shown to provide long-term improvements in pain and functional recovery. However, in the management of severe bilateral fractures of the sacral alae, as were evident in this patient, it is possible that PMMA may fail to sufficiently stabilize micromotion of the fracture plane, preventing complete bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…A surprising finding, however, was that reactive cells, including macrophages, lymphocytes, giant cells and occasionally histiocytes, reappeared after 2 years. Since bone cement attracts macrophages (Rostoker et al 1979, Freeman et al 1982, Linder and Hansson 1983, Levack et al 1989, their presence was not alarming. On the other hand, the presence of giant cells and histiocytes is a clear indication of foreign body reaction.…”
Section: Discussionmentioning
confidence: 99%